Konsep Pemikiran Pendidikan Akal Ibnu Sina pada Anak Pra Aqil Baligh - Elbina Mamla Saidah; Hery Kiswanto; Zainul Muflihin (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2021)
Baligh is the last stage of development of an individual according to the perspective of Islamic studies. This means that if a person has reached puberty, then a child is said to be mature physically, intellectually and emotionally as mentioned by Abu Zahrah that child development is divided into 4 stages, namely first Ash-Shobiy or At-Tifl (small children), second Mumayyiz (able to distinguish something), the third is Cheapiq (towards the age of puberty) and the fourth is Baligh. Ibn Sina was a polymath, who gave birth to many works of thought, including in the field of Education. Several studies on Ibn Sina's educational thoughts have been widely explored and published. Idris Irsyad revealed Ibn Sina's concept of goals, curriculum, methods and how to become a competent teacher. This research uses a literature study method, the object of this research is the concept of reason according to Ibn Sina. The method of data collection is a literature study by carrying out literal descriptions that support theories about intellectual education that affect pre-aqil baligh children.